(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
There is a growing public concern over the potential accumulation of heavy metals in agricultural soils owing to rapid urban and industrial development and increasing reliance on agrochemicals in the last several decades. Excessive accumulation of heavy metals in agricultural soils may not only result in environmental contamination, but elevated heavy metal uptake by crops may also affect food quality and safety. The present study aims to study heavy metal concentrations in rice parts (root, stem, leaf, seed and corresponding soils in the Auyo rice field. Specimens of rice plant parts from different locations in 10 Ã— 10 m were sampled with their corresponding soils. Soil and plant specimens were analysed by using Atomic Absorption spectrometry. It was found that metal concentration in soil was highly variable while the concentration of metals in plants directly depends on the concentration of metal-based pesticide applied. Roots showed the highest metal concentration, followed by leaves, stem and seeds. The physicochemical parameters of the soil from the study area revealed that the pH of the soil sample is within the alkaline range. Similarly, the electrical conductivity was less than 4 (0.51 to 0.65 dSm-1), indicating the presence of soluble salts within average, dissolved Nitrogen at a range of 179.4 to 221 kg/Ha, showing low in nitrogen content, Phosphorus levels in the study region range from 29.00 to 42.33 kg/ha, while potassium level in the soil varies from 126.22 to 250 kg/ha. In general, the soil in the study area was found to be very rich and fertile for the cultivation of rice. The accumulation of some heavy metals in some rice parts may be due to the effects of cypermethrin pesticides.